2011
DOI: 10.1525/jer.2011.6.4.84
|View full text |Cite
|
Sign up to set email alerts
|

What Women Who Use Drugs Have to Say about Ethical Research: Findings of an Exploratory Qualitative Study

Abstract: Drug users are generally seen as a vulnerable population requiring special protection in research; however, to date there has been little empirical research into the ethics of research with illicit drug users. Moreover, the available research has tended to treat "drug users" as a homogeneous category, and has failed to consider potential gender differences in users' experiences. Drawing on focus groups with twenty-seven female drug users in Vancouver, Canada, this study examines women's experiences of research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 52 publications
(92 reference statements)
2
70
1
Order By: Relevance
“…To this end, we suggest that research compensation be provided in cash form, as participants are partaking in what they view as a transactional process that necessitates compensation in exchange to meet their own material needs. As suggested by Bell and Salmon (2011), researchers should consider compensation that is comparable with additional opportunities of income, thus mitigating potential threats to voluntary consent. In addition, our findings highlight the need for transparency around compensation amount, method, and rationale, which should be conveyed to the various members of the research apparatus (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we suggest that research compensation be provided in cash form, as participants are partaking in what they view as a transactional process that necessitates compensation in exchange to meet their own material needs. As suggested by Bell and Salmon (2011), researchers should consider compensation that is comparable with additional opportunities of income, thus mitigating potential threats to voluntary consent. In addition, our findings highlight the need for transparency around compensation amount, method, and rationale, which should be conveyed to the various members of the research apparatus (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how research compensation practices shape individuals’ participation is particularly relevant in the context of PLHIV who use drugs, as such constraints can deter their participation in research that may be of benefit to them or their communities (Bell & Salmon, 2011; Permuth-Wey & Borenstein, 2009). Moreover, concerns regarding the impact of compensation on structurally vulnerable populations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This research suggests that research participation becomes enmeshed in the informal economies of economically disadvantaged communities and provides drug users with an important additional source of income (Bell and Salmon, 2011;Bourgois and Schonberg, 2009;Salmon et al, 2010;Slomka et al, 2007). In this respect, research participation may actually keep drug users out of 'harm's way' by temporarily negating the necessity of engaging in other potentially more hazardous ways of earning money, such as survival sex or crime (Bell and Salmon, 2011;Slomka et al, 2007).…”
Section: Assumption: Paying Drug Users To Participate In Research Is mentioning
confidence: 99%
“…In fact, the profusion of research among the impoverished neighbourhood was found to be seemingly welcomed, as it represented an important income source. Similarly, others have found incentivized research to be favourable among those who are economically disadvantaged as it contributes to an "informal economy" (Bell & Salmon, 2011;Slomka et al, 2007), albeit only temporarily and superficially (Salmon, Browne, & Pederson, 2010). Interestingly, to the best of our knowledge, this research is the first of its kind to report such willingness among Indigenous Peoples to participate in research.…”
Section: "Where Does All This Information Go?" the Practice Of (Un)inmentioning
confidence: 63%